Systematic Review of Patient-Centered Outcomes Following Lower Extremity Flap Reconstruction in Comorbid Patients - Economides, James M.; Patel, Ketan M.; Evans, Karen Kim; Marshall, Elizabeth; Attinger, Christopher E. (Journal of Reconstructive Microsurgery, 2013)
Background Lower extremity soft tissue defects pose a challenging problem to patients with comorbidities. Reconstruction with tissue transfer offers an effective alternative to amputation in this population. Although abundant with data on success and complication rates, the literature has not focused on assessing patient-centered outcomes of these reconstructive procedures.Methods A systematic review was performed by searching an electronic database for relevant studies. The full text of relevant articles was retrieved and the reference lists of those articles reviewed. Single case reports or articles reporting data on wounds sustained from trauma were excluded.Results In total, 318 articles were identified. After applying inclusion and exclusion criteria, 50 articles reporting data on 1,079 flaps remained for inclusion in this review. Ambulation outcomes were reported by 35 articles with a weighted mean rate of postoperative ambulation of 77.4%. Postoperative time to ambulation ranged from an average of 9 months to 22 months. Quality of life and patient satisfaction outcomes were infrequently and inconsistently reported in the literature.Conclusion There is a dearth of patient-centered outcomes for lower extremity flap reconstruction currently in the literature. A standardized method to assessing patient-centered outcomes should be employed to better understand the effectiveness of these procedures.Level of Evidence III Therapeutic
Keywords: lower extremity reconstruction; tissue transfer procedures; patient-reported outcomes